2000
DOI: 10.1038/79876
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic variation in the gene encoding calpain-10 is associated with type 2 diabetes mellitus

Abstract: Type 2 or non-insulin-dependent diabetes mellitus (NIDDM) is the most common form of diabetes worldwide, affecting approximately 4% of the world's adult population. It is multifactorial in origin with both genetic and environmental factors contributing to its development. A genome-wide screen for type 2 diabetes genes carried out in Mexican Americans localized a susceptibility gene, designated NIDDM1, to chromosome 2. Here we describe the positional cloning of a gene located in the NIDDM1 region that shows ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

39
968
16
24

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,348 publications
(1,047 citation statements)
references
References 49 publications
39
968
16
24
Order By: Relevance
“…Thr504Ala) or may affect the levels of expression of calpain-10, e.g. SNP-43 in fat and skeletal muscle [2,4,28,29]. The novel finding of the present study was that SNP-43 affects intra-abdominal obesity and insulin sensitivity in offspring of patients with type 2 diabetes (Study I).…”
Section: Subjects Inmentioning
confidence: 56%
See 2 more Smart Citations
“…Thr504Ala) or may affect the levels of expression of calpain-10, e.g. SNP-43 in fat and skeletal muscle [2,4,28,29]. The novel finding of the present study was that SNP-43 affects intra-abdominal obesity and insulin sensitivity in offspring of patients with type 2 diabetes (Study I).…”
Section: Subjects Inmentioning
confidence: 56%
“…Abdominal obesity is a major risk factor for insulin resistance and type 2 diabetes [1]. Genetic variation in the calpain 10 gene (CAPN10) is associated with type 2 diabetes [2]. Calpain-10 is a calcium-activated protein expressed in all human tissues [3], but the biochemical and physiological mechanism(s) by which it affects the risk of type 2 diabetes remain unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2000 a genome wide scan for type II diabetes susceptibility genes in a population of Mexican Americans identified the calpain 10 gene (CAPN10) as a putative type 2 diabetes susceptibility gene [4]. Since then, multiple other studies involving diverse populations have supported this finding, while others have not [7].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, rabbit mitochondrial calpain 10 has a mitochondrial targeting sequence and is responsible for Ca +2 -induced cleavage of Complex I proteins NDUFV2 and ND6. Horikawa et al [4] described the genetics of human CAPN10, specifically the ability of the gene to undergo alternate splicing, yielding eight potential gene products of varying size. To date there has not been conclusive evidence that the protein products of CAPN10 splice variants are expressed, although multiple investigators have identified immunoreactive bands that correspond to the predicted molecular weight of the splice variants [12;13;14].…”
Section: Introductionmentioning
confidence: 99%